Mapeamento das informações necessárias para subsidiar a avaliação de programas de pós-gradução - Guimaraes, Leonardo Braga (2019)
Scientific, technological and social development is directly associated with information. It represents a guarantee of freedom, enhancing in man his ability to choose, to decide for himself and for society. Information and Communication Technologies (ICT) are part of this context and are the object of investigation by many scholars, especially regarding how we relate to these technologies, either as individuals or as organizations. In public institutions, specifically in universities, ICT presents themselves as challenges and at the same time has enabled significant changes mainly in the planning, organization, representation, preservation, use and dissemination of the knowledge produced in the Graduate Programs. Thus, considering the volume of information produced by postgraduate programs, the problem of this research is: What are the data requirements for structuring a postgraduate information system of a higher education institution from coexistence with the CAPES evaluation system? The institutions chosen for the research refer to the Federal University of Espírito Santo (UFES) and the Postgraduate Program in Public Management (PPGGP-UFES). The choice for UFES is based on the university's consolidated position in its graduate programs and the author's experience in developing UFES systems. This research is characterized as descriptive bibliographic and analytical for the theoretical and methodological investigation of the topics addressed, with qualitative approach and applied research, for the analysis of PPGGP-UFES and CAPES information collection systems. The results point to the importance of integrating postgraduate data as a necessity for institutions that aim for the transparency of their activities and good management practices for postgraduate information. As future work the development of data warehouse model and information dissemination model.